The External Auditors' Policy After The COVID-19 Pandemic and The Accounting Outlook in Tunisia - Assawer Elaoud; Anis Jarboui (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - The objective of this article is to help external auditors resume their activities and enhance their foresight strategy. Specifically, it aims to identify variables that contribute to improved auditors activities primarily post-COVID. Motivation - In light of the challenges presented by the coronavirus pandemic to the global economy, a number of specific lessons can be drawn from this situation. Idea - This research examines the audit mission strategy in which the focus is placed on the spirit and prospective reflection of external auditors. Data - This study uses a qualitative method for collecting information based on non-structured interviews. Tools - The method used in this research is based on cognitive mapping, which makes it possible to analyze the prospective strategies after the COVID-19 pandemic. Indeed, the cognitive map helps to clarify the mental orientation of a person and to visualize some ideas and beliefs on the achievement of their objectives. Findings - The obtained results showed that "digitization and Technology" are the most influential variables in the thinking of the external auditors as they represent the evolution during the COVID-19 period while "communication, the quality of audit social mission and the number of clients", which are the most dependent, represent the objectives to be achieved while the variables "teleworking, teleconference and E-learning" are the means to achieve these objectives. Contribution: This research could raise awareness of the positive outcomes of the COVID-19 era and develop a future work strategy.
Keywords: M40; 650; after COVID-19; digital evolution; prospective strategies; social distancing; external auditors